The performance of Agbabu natural bitumen modified with polyphosphoric acid through fundamental and Fourier transform infrared spectroscopic investigations. (December 2016) - Olabemiwo, Ojeyemi M.; Esan, Akintomiwa O.; Adediran, George O.; Bakare, Hassan O.
Abstract: Nigeria is greatly endowed with large deposit of natural bitumen at Agbabu, Ondo State. The country was reported to have a proven reserve of about 42.47 billion tonnes of bitumen, a quantity which is estimated to be second largest in the world but yet to be explored for economic purposes. However, literature has shown paucity of research work on its modification. This study is therefore carried out to investigate the suitability of polyphosphoric acid (PPA) as a modifier in Agbabu natural bitumen (ANB). The performance of unmodified and PPA modified ANB has been comparatively studied with specific emphasis on Fourier Transform Infrared investigation and fundamental physical tests like penetration, softening point, fire and flash point and specific gravity. Kinematic viscosity (flow) test was also investigated. Penetration indexes of ANB samples were calculated from the penetration values for softening points. The comparative study of FTIR spectra of both base ANB and PPA modified ANB samples showed appearance of some few new peaks in the infrared spectra of PPA modified ANB samples confirming that the structure of the neat ANB had been modified. On the basis of our experimental results, incorporation of PPA up to 6% into ANB structure greatly enhances the fundamental physical and flow properties of ANB. This showed that PPA has the potential of improving the service life of ANB.